The Effect of Feeding a Mixture of Indigofera Flour In Commercial Feeding on The Production and Quality of Quail Eggs (Cortunix-cortunix Japonica) - Isramuddin; Mustaqim; Suryani (Warmadewa University Press, 2024)
Indigoferais a legume plant that has long been known to the Indonesian people, especially on the island of Java. Several Indigofera species that are known to have an important role as feed ingredients include; Indigofera zollingerina. One of the livestock animals that has growth potential using Indigofera leaf flour is quail. This research aims to determine the effect of giving a mixture of Indigofera flour in commercial feed on feed consumption and egg production of quail. This research was carried out at Pak Rusdi's farm, Cot Jabet Village, Gandapura District, Bireuen Regency for 45 days starting in May - July 2023. The design used in this research was a Completely Randomized Design (RAL) with 4 treatments and 3 replications. The results of the research can be concluded that the effect of giving a mixture of Indigofera flour in commercial feed showed no significant difference (P<0.05) on feed consumption, egg production and quail egg quality. The highest average feed consumption was seen in the P2 treatment, namely 23.09 g/head/day and the lowest average was in the P3 treatment, namely 23.07 g/head/day, the highest average quail egg production was in the P2 treatment, namely 77.62% and The lowest average was found in the P3 treatment, namely 75.24%, while the quality of quail eggs included egg weight and egg shell thickness. The highest average egg weight was in treatment P2, namely 8.24 g/item and the lowest value was in P3, namely 7.94 g/item. The highest average eggshell thickness was found in P0, namely 0.14 mm, and the lowest average was in treatments P1 and P3, namely 0.12 mm each.